Analisis Efisiensi Perbankan Syariah Di Malaysia Dengan Pendekatan Maqashid Sharia - Devi Hardianti Rukmana (LAN TABUR : Jurnal Ekonomi Syariah, 2022)
This study aims to determine the significant level of efficiency between Islamic banks in Malaysia using the DEA method and analyze the financial performance of Islamic banking with the Maqashid Syariah approach in Malaysia using the DEA method. The population in this study is Islamic Banks in Malaysia. This research was conducted during the period 2011-2015, selected 9 Islamic banks in Malaysia which became the research sample. The data analysis used in this study is Data Envelopment Analysis (DEA). The results of this study show that Islamic banks in Malaysia that have experienced efficiency over the past 5 years in terms of distribution are Affin Islamic Bank Berhad, CIMB Islamic Bank Berhad, and RHB Islamic Bank Berhad, while those in terms of profitability are Affin Islamic Bank Berhad and in terms of personal income, no one has experienced efficiency.